Anaesthetic Considerations in Patients with Cutis Laxa: Our Experience - K., Dr Sheetal; R., Dr Nandini; R., Dr Chandrika Y. (International Journal of Innovative Research in Medical Science, 2019)
Cutis laxa is a rare, inherited or acquired connective tissue disorder. It is characterized by loose, inelastic skin and various systemic involvements. Cutis laxa type III, described as de Barsy syndrome presents with ophthalmic opacification, skeletal involvement, cardiovascular involvement, mental and growth retardation. Intraoperative hyperthermia of the non-malignant variety with tachycardia is seen in 10% cases of cutis laxa type III. Given the rarity of cutis laxa syndrome, all cases require core and peripheral temperature monitoring.